BOOK REVIEWS (Journal of Finance, 1959)
Book reviewed in this article: Insurance: Comprehensive Medical Services under Voluntary Health Insurance . By B enjamin J. D arsky , N athan S inai , and S olomon J. A xelrod . Cost Estimation Methods in Unemployment Insurance, 1909–1957 . By H arry M alisoff . Development of Comprehensive Insurance for the Household . By J ohn E ugene P ierce . International Finance: Financing Free World Trade with the Sino‐Soviet Bloc . By R aymond F. M ikesell and J ack N. B ehrman . International Financial Transactions and Business Cycles . By O skar M orgenstern . Investments: “… of the People by the People …” By E. H. D avis . Making Profits in the Stock Market . By J acob O. K amm . Investment Analysis . By J ohn H. P rime . Money and Banking: Business Forecasting . By E lmer C. B ratt . Interbank Deposits: The Purpose and Effects of Domestic Balances, 1934–54 . By K atherine F inney . Inflationen: Das Drama der Geldentwertungen vom Altertum bis zur Gegenwart . By R ichard G aettens . Some Monetary Problems—International and National . By P er J acobsson . Bankers and Pashas . By D avid S. L andes . Managed Money at the Crossroads: The European Experience . By M elchior P alyi . Bank Credits and Acceptances . By W ilbert W ard and H enry H arfield . Public Finance, Politique financière . By A lain B arrère . The Economic Theory of Fiscal Policy . By B ent H ansen . Federal Lending and Loan Insurance . By R. J. S aulnier , H arold G. H alcrow , and N eil H. J acoby . Assignment of Income . By D on J. S umma . Income Tax Differentials: Tax Institute Symposium. Accelerated Amortization . By D avid A. T homas . The Self‐supporting City . By G ilbert M. T ucker . Real Estate Finance: Real Estate Principles and Practices . By P reston M artin . Rental Housing: Opportunities for Private Investment . By L ouis W innick .